2014
DOI: 10.1007/s11033-014-3824-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in nucleotide excision repair genes and susceptibility to colorectal cancer in the Polish population

Abstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive disease that is associated with a severe deficiency in nucleotide excision repair. Genetic polymorphisms in XP genes may be associated with a change in DNA repair capacity, which could be associated with colorectal cancer development. We assessed the association between 94 single nucleotide polymorphisms (SNPs) within seven XP genes (XPA–XPG) and the colorectal cancer risk in the Polish population. We genotyped 758 unselected patients with colorectal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
2
22
1
1
Order By: Relevance
“…The results from three studies were similar to ours [25,28,29]. Interestingly, Steck et al [28] reported a significantly positive association between this polymorphism and CRC risk in African Americans, while another study demonstrated an association in the reverse direction in Caucasians [27]. Several meta-analyses on the association between these two polymorphisms and CRC risk have been published [8,10,31].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results from three studies were similar to ours [25,28,29]. Interestingly, Steck et al [28] reported a significantly positive association between this polymorphism and CRC risk in African Americans, while another study demonstrated an association in the reverse direction in Caucasians [27]. Several meta-analyses on the association between these two polymorphisms and CRC risk have been published [8,10,31].…”
Section: Discussionsupporting
confidence: 78%
“…When compared with the XPC rs2228001 A > C polymorphism, relatively fewer studies have examined the association of the rs2228000 C > T polymorphism with CRC susceptibility [25,27,28,29]. The results from three studies were similar to ours [25,28,29].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have reported that XPG gene polymorphisms are associated with different kinds of cancers (Liu et al, 2014;Mirecka et al, 2014;Steck et al, 2014;Xu et al, 2014;Paszkowska-Szczur et al, 2015). In this paper, we conducted a casecontrol study to investigate the role of three common single nucleotide polymorphisms (SNPs) in the XPG gene (rs2094258, rs751402 and rs17655) in the development of gastric cancer in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Los polimorfismos gené-ticos de las enzimas implicadas en estos procesos de reparación van a determinar su capacidad funcional, pudiendo conducir a una menor capacidad de reparación del ADN, que puede ser la base de una tasa de mutación más alta, y como consecuencia última provocar un aumento de riesgo de desarrollo de procesos tumorales [33][34][35] . Los polimorfismos en ERCC1 y ERCC2 han sido asociados a un mayor riesgo para el desarrollo de cáncer de piel, cáncer de mama y cáncer colorectal [36][37][38][39][40] .…”
Section: Metabolismo Hidrocarburos Aromáticos Presentes En El Humo Deunclassified